2004
DOI: 10.1002/adfm.200400109
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nanostructuring on the Thermal Conductivity of Thermoelectric CoSb3

Abstract: The high concentration of grain boundaries provided by nanostructuring is expected to lower the thermal conductivity of thermoelectric materials, which favors an increase in their thermoelectric figure‐of‐merit, ZT. A novel chemical alloying method has been used for the synthesis of nanoengineered‐skutterudite CoSb3. The CoSb3 powders were annealed for different durations to obtain a set of samples with different particle sizes. The samples were then compacted into pellets by uniaxial pressing under various co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
190
4
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(218 citation statements)
references
References 37 publications
(43 reference statements)
18
190
4
1
Order By: Relevance
“…Having a synthesis route with high yield, reproducibility and low energy consumption is one of the key issues that have to be tackled and overcome. Chemical synthesis routes usually take less energy, time and have less impact on environment [5,6]. CoSb 3 , known as skutterudites, exhibit high TE figure of merit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having a synthesis route with high yield, reproducibility and low energy consumption is one of the key issues that have to be tackled and overcome. Chemical synthesis routes usually take less energy, time and have less impact on environment [5,6]. CoSb 3 , known as skutterudites, exhibit high TE figure of merit.…”
Section: Introductionmentioning
confidence: 99%
“…Iron substituted CoSb 3 , FexCo 1-x Sb 3 , have been reported to display good performance as a p-type TE material, in terms of its TE figure of merit (ZT), and abundance of the constituent elements [8][9][10][11][12][13][14]. The ZT can be improved via introduction of dopants, nanoengineering and in case of skutterudites, introducing rare earth elements in the crystal cages to reduce the thermal conductivity [1,[4][5][6] due to rattling of the fillers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are observing very similar reductions in thermal conductivity to those of the Si nanowires with a roughened surface as reported in Refs. [12] and [13]. Previously, Chen also addressed the effect of interface roughness on the crossplane thermal transport in a superlattice structure [30].…”
Section: Resultsmentioning
confidence: 99%
“…They asserted that the embedded nanostructures allow a filtering effect that allows the 'alloy lower limit' to be overcome in the reduction of the thermal conductivity. Toprak et al also observed a substantial reduction in the thermal conductivity of CoSb 3 with decreasing grain size in the nanometer region [12]. A ZT value of 1.4 in BiSbTe alloy was reported lately, in which the authors believed that the ZT improvement is the result of low thermal conductivity caused by the increased phonon scattering by grain boundaries and defects [13].…”
mentioning
confidence: 90%